2018
DOI: 10.1016/j.jphotobiol.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two functionalized fullerenes for antimicrobial photodynamic inactivation: Potentiation by potassium iodide and photochemical mechanisms

Abstract: A new fullerene (BB4-PPBA) functionalized with a tertiary amine and carboxylic acid was prepared and compared with BB4 (cationic quaternary group) for antimicrobial photodynamic inactivation (aPDI). BB4 was highly active against Gram-positive methicillin resistant Staphylococcus aureus (MRSA) and BB4-PPBA was moderately active when activated by blue light. Neither compound showed much activity against Gram-negative Escherichia coli or fungus Candida albicans. Therefore, we examined potentiation by addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
0
28
0
1
Order By: Relevance
“…Some research groups that studied the use of PSs with KI in aPDT stated that, when a PS is used in combination with KI, it is necessary to have lower PS concentration or lower light exposure than when used in non-combined strategies [15,36,[38][39][40][41][47][48][49]. The potentiated effect of RB by KI was studied in the photoinactivation of E. coli and S. aureus [36,41].…”
Section: Photodynamic Inactivation Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research groups that studied the use of PSs with KI in aPDT stated that, when a PS is used in combination with KI, it is necessary to have lower PS concentration or lower light exposure than when used in non-combined strategies [15,36,[38][39][40][41][47][48][49]. The potentiated effect of RB by KI was studied in the photoinactivation of E. coli and S. aureus [36,41].…”
Section: Photodynamic Inactivation Assaysmentioning
confidence: 99%
“…Some studies have shown that KI also enhances the effect of other PS classes [36,[38][39][40][47][48][49]. The potentiated effect of KI was observed for porphyrin-based PSs, Photofrin [40] and, for a formulation constituted by five cationic porphyrin derivatives [15], in the photoinactivation of gram-negative and gram-positive bacteria.…”
Section: Photodynamic Inactivation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that different organic salts can improve the efficiency of aPDT against Gram-negative bacteria ( Huang et al, 2012 ; Kasimova et al, 2014 ). Recently, some studies have demonstrated that aPDT can be potentiated by addition of several different inorganic salts, such as sodium bromide ( Wu et al, 2016 ) sodium azide ( Huang et al, 2012 ; Kasimova et al, 2014 ), sodium thiocyanate ( St Denis et al, 2013 ) and potassium iodide ( Vecchio et al, 2015 ; Zhang et al, 2015 ; Freire et al, 2016 ; Huang et al, 2016 , 2017 , 2018a , c ; Hamblin, 2017 ; Reynoso et al, 2017 ; Wen et al, 2017 ). In fact, the addition of iodide has been shown to improve the efficiency of aPDT in several animal models of localized infection.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was also efficient in aPDT of Gram-negative and Gram-positive bacteria mediated by Rose Bengal ( Wen et al, 2017 ) and fullerenes ( Huang et al, 2018b ). Interestingly, an anionic porphyrin in the presence of KI was able to photoinactivate E. coli ( Huang et al, 2018a ). The combination of MB and KI was also efficient to treat an urinary tract infection in a female rat model ( Huang et al, 2018c ).…”
Section: Introductionmentioning
confidence: 99%